The Influence of the Dynamics of Literary Criticism on Literary Works in the Umayyah Period - Febrianisa, Sindy; Nazar, Muhammad (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
The development of literature has been very rapid up to modern times. makes us aware that this rapid development occurred because of pre-modern times which spread literature to the stage it is today. especially with criticism of literature itself, viewed from the perspective of the glory that occurred during the Umayyah era, it had a very, very clear impact even to the point of criticizing literary works themselves. The research will be carried out using a historical approach and then data collection will be carried out using the library method. The results of the research that has been carried out are that literary criticism during the Jahiliy era only emphasized the qofiyah aspect and vocal sounds. Meanwhile, literary criticism during the Umayyad period had developed to the point that research was seen in terms of language and literature itself. during the Umayyah era there were the best poets such as Al-Farazdaq, Jarir and Al-akhtal